Estereoultraestructura del pulmón de anuros bufónidos : I. Bufo arenarum - Hermida, Gladys (1994)
Scanning electron microscopy was used to determined the inner morphology of the Bufo arenarum lung. The observations let conclude that the lung presents three types of folds which divide the organ into alveolar spaces. The inner surface of the lung, as well as the lateral wall of the folds are lined with respiratory epithelium, except in the apex of the primary folds (ciliated surface with goblet cells) and in the secondary folds (ciliated surface).